Massive Pulmonary Thromboembolism In A Sarcoidosis Patient: Case Report - Ismail Hanta; Ezgi Ozyilmaz; Oya Baydar; Sedat Kuleci; Ali Kocabas (Cukurova Medical Journal, 2011)
Although sarcoidosis is not a well known risk factor of pulmonary thromboembolism, recent investigations shows increased risk of pulmonary thromboembolism in these patients with the lack of any other risk factor. In this case report, massive pulmonary embolism was presented in a forty seven years old female patient who is followed up under metilprednisolon therapy due to sarcoidosis for five months. This patient was underlined because of that sarcoidosis may be a potential risk factor of pulmonary thromboembolism and must be kept in mind at the patients with sarcoidosis and acute deletoration. Keywords: [Cukurova Med J 2011; 36(1): 37-40]